ASP.NET core recipes : a problem-solution approach - Ciliberti, John (Apress, 2017)
ASP.NET Core Recipes is a practical guide for developers creating modern web applications, cutting through the complexities of ASP.NET, jQuery, React, and HTML5 to provide straightforward solutions to common web development problems using proven methods based on best practices. The problem-solution approach gets you in, out, and back to work quickly while deepening your understanding of the underlying platform and how to develop with it. Author John Ciliberti guides you through the MVC framework and development tools, presenting typical challenges, along with code solutions and clear, concise explanations, to accelerate application development. Solve problems immediately by pasting in code from the recipes, or put multiple recipe solutions together to overcome challenging development obstacles.